Capacity of underwater optical wireless communication systems over salinity-induced oceanic turbulence channels with ISI - Boluda-Ruiz, Rubén; Salcedo-Serrano, Pedro; Castillo-Vázquez, Beatriz; García-Zambrana, Antonio; Garrido-Balsells, José María (Optica Publishing Group, 2021)
Point-to-point underwater optical wireless communication (UOWC) links are mainly impaired by scattering due to impurities and turbidity in the open water, resulting in a significant inter-symbol interference (ISI) that limits seriously both channel capacity and the maximum practical information rate. This paper conducts, for the first time, the channel capacity analysis of UOWC systems in the presence of ISI and salinity-induced oceanic turbulence when the undersea optical channel is accurately modeled by linear discrete-time filtering of the input symbols. In this way, novel upper and lower bounds on channel capacity and mutual information are developed for non-uniform on-off keying (OOK) modulation when different constraints are imposed on the channel input. The results show that the capacity-achieving distribution, which is computed through numerical optimization, is discrete and depends on the optical signal-to-noise-ratio (SNR). Moreover, a non-uniform input distribution significantly improves the channel capacity of such systems affected by ISI and oceanic turbulence, especially at low optical SNR. Monte Carlo techniques are employed to test the developed bounds for different undersea optical channels with one, two and three casual ISI coefficients.
Keywords: Fotónica; Optoelectrónica; Optical scattering; Computational modeling; Wireless communication; Monte Carlo methods; Photonics; Dispersion; Underwater optical wireless communication (UOWC); Channel impulse response (CIR); Henyey-Greenstein model; Monte-Carlo simulation